Soil quality and vulnerability in a Mediterranean natural ecosystem of Central Italy. - Francaviglia, R.; Gataleta, L.; Marchionni, M.; Trinchera, A.; Aromolo, R.; Benedetti, A.; Nisini, L.; Morselli, L.; Brusori, B.; Olivieri, P.; Bernardi, E. (Chemosphere, 2004)
Wet and dry atmospheric depositions and soil chemical and microbiological properties were determined in a Mediterranean natural ecosystem of Central Italy near Rome (Castelporziano Estate). The monitoring of depositions permitted us to quantify the exceedances of S and N compounds (expressed as eqH(+)ha(-1)year(-1)) over the critical loads of acidity. Critical loads, i.e. the quantity of a substance which a part of the environment can tolerate without adverse effects occurring, were determined adopting the level 0 methodology following the UN/ECE Convention on Long-range Transboundary Air Pollution. Deposition data were available for the period 1992-1997, and acidity exceedances were referred to the main vegetation types present in the area. Results showed that most part of the Estate has a medium degree of vulnerability to acidification, and the corresponding risk of acidification deriving from the exceedances of atmospheric deposition was rather low. The study of soil chemical and microbiological properties included mainly total soil organic carbon (SOC), microbial biomass-C, biomass-C/SOC, soil respiration, and metabolic quotient (qCO2). Soil organic C metabolism has been discussed on the basis of the results from eight sampling sites.
The following values have no corresponding Zotero field: accession-num: 14987944
Keywords: Acidification; Atmospheric depositions; Biological indicators; Critical loads; Soil microbial biomass; Soil organic carbon

Biological and biochemical indicators in derelict soils subject to erosion - Garcia, C.; Hernandez, T. (Soil Biology and Biochemistry, 1997)
n 21 derelict soils from a semi-arid Spanish Mediterranean area, with a lithological sub- strate of Ioams, submitted to a high degree of erosion, several biological and biochemical properties in- dicative of the soil degradation leve1 were determined. The organic matter content of these soils was very low (mean value = 11.8 g kg-‘), approximately one-third of the average value for organic matter content of natura1 soils in the same zone. Biological properties such as basal respiration and biomass C also had low values and were positively correlated with the organic matter content. Low values for de- hydrogenajse and catalase activity were indicative of low biological activity of the degraded soils. A positive correlation was found between the hydrolases related with the N, P, C and S cycles (urease, proteases, fl-glucosidase and arylsulphatase), as wel1 as between these hydrolases and the organic matter content. Principal component analysis showed that ah the variables studied, except catalase and qCOr, had a similar behaviour. There was a negative correlation between many of the properties studied and electrical conductivity, which agreed with the higher degree of biological and biochemical degradation found in gypsiferous soils with a higher salt content. Arylsulphatase and p-glucosidase activity were the hydrolases most affected by soil erosion processes
Keywords: biochemical parameters (PG); Biological indicators; derelict soils; Soil degradation